Cesarean analgesia using levobupivacaine continuous wound infiltration: a randomized trial. (November 2015) - Jolly, Claude; Jathières, François; Keïta, Hawa; Jaouen, Envel; Guyot, Bernard; Torre, Antoine
Abstract: Objective: Neuraxial morphine is considered as a "gold standard" for pain relief after cesarean section, however it causes bothersome side effects. Alternative analgesia including nonsteroidal antiinflammatory drugs (NSAID) has been proposed. We aimed to assess the morphine sparing effect of continuous wound infiltration with a local anesthetic, when added to multimodal systemic analgesia including NSAID without subarachnoid morphine. Study design: Sixty-eight women scheduled for elective cesarean section under spinal anesthesia were included in a randomized controlled open-label trial. Patients received bupivacaine spinal anesthesia without intrathecal morphine. Postoperative analgesia consisted for all patients in multimodal systemic analgesia with acetaminophen, nefopam, celecoxib, and patient-controlled intravenous morphine for 24 h. The intervention group also received subfascial levobupivacaine infiltration through a multi-holed catheter, at 6.25 mg/h for 48 h. The primary endpoint was total morphine consumption at 24 h postoperatively; and secondary endpoints were pain scores, side effects, breastfeeding comfort, maternal satisfaction, and nurse workload. Student t test, Mann–Whitney test or χ 2 test were used when appropriate. Results: The intervention group had 6.7 mg less morphine consumption (95%CI −1.3 mg; −12 mg, P = 0.02), and 0.8 pain point less at rest on the numerical rating scale 0–10 (95%CI −0.3; −1.3, P = 0.002). The intervention was associated with significantly better breastfeeding comfort (+1.7 at numerical rating scale score 0–10, 95%CI +0; +3.3, P = 0.0498). Wound dressing changes were required in a significantly higher proportion of intervention-group women (12/34 vs. 1/34, P = 0.002). Conclusion: Adding continuous levobupivacaine infiltration to multimodal analgesia after cesarean section without subarachnoid morphine decreased postoperative morphine consumption and pain, facilitated breastfeeding initial comfort, and slightly increased nurse workload.